A new vision for New Orleans and the Mississippi delta: applying ecological economics and ecological engineering. Issue 9 (1st November 2006) - Costanza, Robert; Mitsch, William J.; Day, John W.
Abstract : The restoration of New Orleans and the rest of the Mississippi delta after Hurricane Katrina can become another disaster waiting to happen, or it can become a model of sustainable development. Sea level is rising, precipitation patterns are changing, hurricane intensity is increasing, energy costs are predicted to soar, and the city is continuing to sink. Most of New Orleans is currently from 0.6 to 5 m (2–15 feet) below sea level. The conventional approach of simply rebuilding the levees and the city behind them will only delay the inevitable. If New Orleans, and the delta in which it is located, can develop and pursue a new paradigm, it could be a truly unique, sustainable, and desirable city, and an inspiration to people around the world. This paper discusses the underlying causes and implications of the Katrina disaster, basic goals for a sustainable redevelopment initiative, and seven principles necessary for a sustainable vision for the future of New Orleans and the Mississippi delta.